Design and Build a Straight Motion Experiment Set With Remote Laboratory Based on the Internet of Things - Arif Farma Putra; - Asrizal; - Yohandri (PILLAR OF PHYSICS, 2022)
The era of the Industrial Revolution 4.0 is an era that has no boundaries to advance science-technology. Experimental tools are currently still using manual tools. The solution for the pandemic is a remote laboratory. Remote Laboratory is a remote laboratory using the internet with real components. This study aims to specification performance, design specifications on the experimental set of Uniform Motion with Remote Laboratory based on internet Of Things. The research carried out is included in engineering research. There are two methods of measuring data, namely direct measurement and indirect measurement. The experimental set has a size of 60x20 cm. The sensor used is infrared avoid obstacle which functions as a counter to the object's travel time. blynk application as tool control center. The Straight Motion experiment set with internet-based Remote Laboratory Of Things has an average accuracy of 98.6 % and an average accuracy of 0.96. The data that has been obtained shows that this experimental set can be used for GLB and GLBB.